Nevi. - Bonifazi, E.; Mazzotta, F.; Garofalo, L. (European Journal of Pediatric Dermatology, 2001)
Nevus is a circumscribed area of the skin, usually consisting of an excess of cutaneous cells. Nevus is usually present at birth or from the first periods of life and persists throughout life in most cases. The definition is uncertain due to numerous factors, the first being the discrepancy between the common meaning of nevus, which exclusively regards the melanocytic nevus, and the dermatological use of the word nevus, including all types of nevi, besides melanocytic nevus. We are now considering the other factors responsible for the uncertain definition of nevus, analysing its definition. (...)